RECONSTRUCTION OF SEGMENTAL MANDIBULAR LOSS WITH VASCULARIZED FREE FIBULA FLAPS - Naqvi, Shahid Hussain; Hameed, Shahid; Aslam, Muhammad Rizwan; Ahmed, Rao Saood; Nafees, Abu ul Ala; Pevaiz, Hafiz Khalid (Journal of Ayub Medical College Abbottabad, 2020)
Background: Various methods for mandibular reconstruction have been demonstrated in literature from autogenous bone graft to free flaps and more recently tissue engineered materials. We share our experience of mandibular reconstruction with free fibular flap and evaluate its efficiency as a viable option for mandibular reconstruction. Methods: It was a cross-sectional study, conducted at Plastic surgery department combined military hospital, Rawalpindi. Study was carried out over a period of two years from November 2016 to November 2018. The data of demography, mode of presentation, pattern of reconstruction and procedural complications of the patients who underwent free fibula flap for segmental mandibular loss, were collected and analysed. Patients with segmental loss of mandible ranging from 6 to 15 cm and those who could sustain surgery were included in the study, while the patients with metastatic malignancy and recurrent disease were excluded from the study. Each patient was called for first follow up after 2 weeks then subsequent follow up after 1 month. Descriptive statistics were done with the help of spss-20. Results: A total of 57 patients with segmental mandibular loss treated with free fibula flap, fulfilling inclusion and exclusion criteria were included in this study. Thirty-eight patients were male while 19 were female with mean age 56±3 years. Cause of mandibular loss was malignancy in 52 (91.2%), trauma in 3 (5.2%), and ameloblastoma in 2 (3.5%) patients. Major complications like flap failure was seen in one (1.75%), bone exposure in 1 (1.75%) and recurrence was observed in 1 (1.75%) patient. Minor complications like hematoma, wound dehiscence and oro-cutaneous fistula were seen in 2, 1 and 3 patients respectively. Conclusion: Free fibular flap shows good functional results with a high degree of consistency, and acceptable complications rate, so it should be the first choice for mandibular reconstruction. Keywords: Mandibular reconstruction; Free fibular flap; Osteo-Cutaneous Flap